2020
DOI: 10.2147/jaa.s273820
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of Chronic Respiratory Health Symptoms and Associated Factors Among Flour Mill Factory Workers in Addis Ababa, Ethiopia, 2019: A Cross-Sectional Study</p>

Abstract: Background: Flour mill workers are at high risk of developing respiratory symptoms due to exposure to flour dust in their working environment. Exposure to flour dust linked with the development of chronic respiratory disorders. However, very little evidence has been available on the respiratory symptoms of exposed workers in large-scale flour mill factories. Therefore, the aim of this study was to assess chronic respiratory health symptoms and associated factors among flour mill workers in Addis Ababa, Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…This study is in line with a study conducted in Tanzania, which stated that previous dusty jobs are three times more likely to have difficulty of breathing and breathlessness as the respiratory health symptoms than free from the previous dusty job [33]. This study is also similar to a study conducted in Ethiopia, which stated that workers who had past dust exposure history were 1.86 times more likely to have at least one chronic respiratory health symptoms than workers who had no past dust exposure history [28]. The reason for the significant association of past occupational dust exposure history with the development of at least one chronic respiratory symptom might be due to misunderstanding and lack of training and knowledge on RPE utilization of workers as well as workers who had experience on dust exposure may ignore in using RPE as they consider themselves adapting the dust.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study is in line with a study conducted in Tanzania, which stated that previous dusty jobs are three times more likely to have difficulty of breathing and breathlessness as the respiratory health symptoms than free from the previous dusty job [33]. This study is also similar to a study conducted in Ethiopia, which stated that workers who had past dust exposure history were 1.86 times more likely to have at least one chronic respiratory health symptoms than workers who had no past dust exposure history [28]. The reason for the significant association of past occupational dust exposure history with the development of at least one chronic respiratory symptom might be due to misunderstanding and lack of training and knowledge on RPE utilization of workers as well as workers who had experience on dust exposure may ignore in using RPE as they consider themselves adapting the dust.…”
Section: Discussionsupporting
confidence: 89%
“…As stated somewhere else in previous study that workers with a previous exposure ignore to use of personal protective equipment because they think they adapt to the dust. This statistical significance could be because the workers might have previously worked in dusty jobs identified to cause the respiratory problem, so this may lead to the aforementioned respiratory tissue physiologic change in later life and exacerbate the occurrence of respiratory symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any item of clothing made up of textile/leather can be worn by the workers to cover their nose/mouth to protect the entry of dust particles. 21 …”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopian flour mill workers, significant risk factors for work-related respiratory symptoms included employment duration >5 years, flour mixing operations, inadequate workplace ventilation, lack of respiratory protective equipment and bakers having no safety training [26][27][28]. Two studies of bakeries in the DR Congo and Benin reported the prevalence of OA as 3.6% and 10% respectively [29,30].…”
Section: Key Pointsmentioning
confidence: 99%